Assessment of acute toxicity of two antiparasitic combined drugs from the group of avermectins and piretroids - V. V. Tokar; M. B. Musaev; T. S. Novik (Российский паразитологический журнал, 2025)
The purpose of the research is to assess the acute toxicity in laboratory animals of experimental samples of two antiparasitic combined drugs from the group of avermectins and pyrethroids, conventionally designated as CA-17 and CA-18 (NBC Pharmbiomed LLC).Materials and methods. The present experiment was performed on sexually mature outbred rats and mice (males), to which the studied drugs were administered in two ways, intragastrically and subcutaneously, in a dose range that allows calculating the parameters of acute toxic effects or setting the maximum tolerated dose. The studied preparations were transparent oily liquids containing avermectin C and cyfluthrin in different concentrations. During 14 days, the condition and behavior of the animals were monitored, death and symptoms of intoxication were recorded. Probit analysis was used to calculate LD50 values and other parameters of acute toxic effects of drugs.Results and discussion. The ЛД50 value of CA-17 when administered intragastrically to rats and mice is 6072 (5208 6975) and 4008 (2340 6094) mg/kg, respectively. The ЛД50 value of CA-18 when administered intragastrically to rats and mice is 3716 (3103 4496) and 2929 (1454 3603) mg/kg, respectively. Compared with rats, mice have a species sensitivity to both drugs. Preparations CA-17 and CA-18 for intragastric administration according to the hygienic classification belong to hazard class 3. The ЛД50 value of CA-17 after cutaneous administration to rats and mice is more than 7,500 mg/kg, respectively. Similar indicators for CA-18 for rats and mice are more than 5,000 and 2,500 mg/kg, respectively. According to the parameters of cutaneous toxicity, both drugs belong to hazard class 4.